Managing Adverse and Reportable Information Regarding General and Flag Officers - Harrell, Margaret C. (RAND Corporation, 2012)
Adverse and reportable information must be considered at the time of assignments, promotions, and retirements of senior military officers. This monograph documents current policies and practices for identifying and considering such information, identifies potential gaps in these processes, and makes recommendations on how to make them more consistent and reliable.